"Dose – effect" calibration dependence by frequency of unstable chromosomic exchanges in human lymphocytes in acute gamma irradiation by 137Сs in low doses for biological dosimetry - V. A. Kurochkina; L. K. Bezdrobna; T. V. Tsyganok; I. A. Khomych (Ядерна фізика та енергетика)
The calibration dependence of dicentrics and rings chromosomes with an accompanying fragment induction in human lymphocytes by in vitro 137Сs acute gamma irradiation of blood in the dose range of 0.09 - 1.0 Gy is presented. The application of the obtained calibration curve for estimation of “biological” doses for overexposed 9 persons from the contract staff of the Chornobyl SSE is shown. Their doses calculated by the frequency of dicentrics and centric rings with consideration of operation duration and mode in the zone of influence of the radiation factor, significantly exceeded the doses determined by the methods of physical dosimetry.